El preludio de la tormenta: Conflictos y movilización social en Nicaragua 2014-2018 - Elvira Cuadra Lira (Confluenze)
In April 2018, a social uprising occurred in Nicaragua with massive protests that lasted until early 2019 when they were crushed by state violence. The protests surprised the government because they expressed discontent that was not perceived to be so widespread or deep. Initial analyses argued that the uprising was impossible to foresee (Marti i Puig 2019; Cabrales 2019); however, for several years before, there had been protests and mobilizations that fed an underground current of discontent. This essay provides an overview of these social actions and analyzes three emblematic cases of emerging actors.